Osteopontin impairs host defense during pneumococcal pneumonia - van der Windt, Gerritje J W; Hoogendijk, Arie J; Schouten, Marcel; Hommes, Tijmen J; de Vos, Alex F; Florquin, Sandrine; van der Poll, Tom (The Journal of infectious diseases, 2011)
Streptococcus pneumoniae is the most frequently isolated pathogen responsible for community-acquired pneumonia. Osteopontin is involved in inflammation during both innate and adaptive immunity. To determine the role of osteopontin in the host response during pneumococcal pneumonia, osteopontin knockout (KO) and normal wild-type (WT) mice were intranasally infected with viable S. pneumoniae. Pneumonia was associated with a rapid increase in pulmonary osteopontin concentrations in WT mice from 6 h onward. Osteopontin KO mice showed a prolonged survival relative to WT mice, which was accompanied by diminished pulmonary bacterial growth and reduced dissemination to distant body sites. In addition, at 48 h after infection pulmonary inflammation was decreased in osteopontin KO mice as reflected by lower inflammation scores and reduced chemokine concentrations. In contrast to pneumococcal pneumonia, osteopontin deficiency did not influence bacterial growth in primary pneumococcal sepsis induced by direct intravenous infection, suggesting that the detrimental effect of osteopontin on antibacterial defense during pneumonia primarily is exerted in the pulmonary compartment. Moreover, recombinant osteopontin stabilized S. pneumoniae viability in vitro. These results suggest that the pneumococcus misuses osteopontin in the airways for optimal growth and to cause invasive disease after entering the lower airways.